2014
DOI: 10.4103/0972-5229.136072
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome and predictors of mortality in children with sepsis, severe sepsis, and septic shock from Rohtak, Haryana: A prospective observational study

Abstract: Background:Information regarding early predictive factors for mortality and morbidity in sepsis is limited from developing countries.Methods:A prospective observational study was conducted to determine the clinical outcome and predictors of mortality in children with sepsis, severe sepsis, and septic shock. Children aged 1 month to 14 years admitted to a tertiary care pediatric intensive care unit (PICU) with a diagnosis of sepsis, severe sepsis, or septic shock were enrolled in the study. Hemodynamic and labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 12 publications
7
36
2
1
Order By: Relevance
“…An Indian study from PGI, Chandigarh also reported high (65.8%) mortality rate in fluid refractory septic shock [15]. Other Indian studies have reported morality rates of 47% from Punjab, 50% from AIIMS, Delhi, 58% from Rohtak, Haryana [8,16,17]. Our findings are in line with other Indian studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…An Indian study from PGI, Chandigarh also reported high (65.8%) mortality rate in fluid refractory septic shock [15]. Other Indian studies have reported morality rates of 47% from Punjab, 50% from AIIMS, Delhi, 58% from Rohtak, Haryana [8,16,17]. Our findings are in line with other Indian studies.…”
Section: Discussionsupporting
confidence: 90%
“…Han YY et al reported that non-survivors were treated with more inotropic therapies as compared to survivors [18]. In a recent study from Rohtak where authors evaluated the hemodynamic and laboratory parameters which discriminated survivors from non survivors, it was found that mortality was not predicted by any individual factor like time lag to PICU transfer, duration of PICU stay, presence of MODS and PRISM score at admission [17]. However this study was limited by the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of invasive ventilation was divided as <72 hours and >72 hours based on a study done in Haryana, which had 72 hours as the maximum duration of invasive ventilation. 3 We divided the cases as after spontaneous and planned extubation and also analysed the causes of reintubation. A complication was attributed to mechanical ventilation if it was not present before and it developed during ventilation.…”
Section: Methodsmentioning
confidence: 99%
“…In practical terms, however, “intensive care” can only be provided where these substantial resources and trained, multidisciplinary personnel are in place. The mere presence of an “intensive care unit” does not guarantee the presence of intensive, integrated care, or good outcomes, as the mortality rates in mixed and exclusively pediatric ICUs in LMICs can be as high as 50–58% ( 22 , 23 ). In any case, ICUs are uncommon in many parts of the world and, with rare exception, most of the world’s sickest children are cared for outside of conventional ICUs (pediatric or mixed) by caregivers without pediatric or critical care training.…”
Section: The Role Of Critical Care Trainingmentioning
confidence: 99%